In Situ conservation of plant genetic resources in home gardens of Southern Vietnam : (International Plant Genetics Research Institute, 1999)
The field study examined fundamental questions about the role of home gardens in conservation, namely how the dynamic nature and multiple uses of home gardens affect the stability of this micro-ecosystem and its role as a viable conservation unit.